A new species of Lippia (Verbenaceae) from the inselbergs of Brazilian Atlantic Forest - Cardoso, Pedro Henrique; Menini Neto, Luiz; Salimena, Fátima Regina Gonçalves (Phytotaxa, 2019)
A new species of Lippia endemic to the Brazilian Atlantic Forest is described and illustrated. Lippia diversifolia is currently known from the inselbergs of Espírito Santo and Rio de Janeiro and is characterized by markedly tetragonal branches, of which the opposed sides are densely strigose and the other glabrescent, with indument alternating in the subsequent internode, leaf blade cartaceous to coriaceous, adaxial surface strigose, abaxial surface tomentose or strigose, peduncle 3.5–9 cm long, bracts strigose with apex acute, inconspicuous calyx, and white sessile glands along the whole plant. We provide field photographs, distribution map, conservation status and a table with the main characters that distinguish it from Lippia rubella, which is a morphologically similar species.